AB0087 Modelling Osteoarthritis in Vitro – Applicability of 3D Scaffold-Free Constructs. (9th June 2015) - Lang, A.; Neuhaus, J.; Barnewitz, D.; Gaber, T.; Ponomarev, I.
Abstract : Background: By 2020, osteoarthritis (OA) will be the fourth leading cause of world's most common disabilities as a result of an increasing life expectancy and an aging population. According to the world health organization (WHO), 9.6% of men and 18% of women aged 60 or older suffer from OA worldwide. The main characteristics of OA are the complex interplay of inflammatory processes and cartilage degradation. To study underlying mechanism and new therapeutic approaches, small animal models are widely used whereas the applicability to the human is questionable. Therefore, during the last years different efforts have been made to effectively apply the three "Rs" – R eduction, R efinement and R eplacement – in animal experimentation that have been stated by Russell & Burch in 1959. Objectives: However, to our knowledge the already existing 3D cell models for OA research are limited to reflect the complex pathogenesis and inconvenient to handle. Based on our scaffold-free 3D cartilage transplant (SFCT) technology (fzmb GmbH), we generated an in vitro OA model that consists exclusively of chondrocytes and their metabolic products. Methods: SFCTs were generated using equine chondrocytes. SFCTs with diameters up to 1.5 cm and thickness between 1-3 mm were treated with IL-1β and TNFα to trigger inflammatory process that parallels arthritic conditions for 3 weeks or left untreated. The treated group of constructs was splitted and either directly fixed after stimulation or treated without stimulation for further 3 weeks in order to evaluate the regeneration potential. Quantitative PCR was performed to investigate an inflammatory and cartilage specific marker profile (IL-1β, TNFα, IL-6, IL-8, Cox-2, MMP-1, MMP-3, MMP-9, BMP-2, SOX-9, TGFβ1) that was normalized to the housekeeper genes (GAPDH, HRPT, SDHA) and standardized to the untreated controls. Results: We observed a significant increase of inflammatory marker expression (IL-1β, TNFα, IL-6, IL-8, Cox-2) and matrix degrading enzyme expression (MMP-1, MMP-3) on RNA level after stimulation with IL-1β and TNFα as compared to the untreated control which was reversible after 3 weeks of regeneration. MMP-9 showed a negative regulation under stimulation. Additionally, BMP-2 showed an up-regulation under stimulation whereas TGFβ1 showed no changes. Furthermore, the down-regulation of SOX-9 indicates phenotypical changes of chondrocytes that were confirmed in preliminary histological investigations. Conclusions: The results from our 3D in vitro OA model indicate osteoarthritic changes that strikingly reflect the observations of early stage OA pathogenesis in humans. Moreover, beside the similarity to native hyaline cartilage the advantage of this model is the extended durability and the possibility to produce constructs in parallel from one human donor facilitating reproducibility. Prospectively, we will focus on the in situ transfer as well as on the transfer of our technology on rheumatic disorders following the meaningful path of implementation of 3R in the scientific community. Disclosure of Interest: None declared